Rupert Brooke’s Neo-Paganism - Tomislav M. Pavlović (University of Belgrade, 2016)
Rupert Brooke (1887-1915) embodies the myth of the Great War but after his sudden death his war poems tended to be disapproved of. His pre war Georgian lines are also dismissed on account of their effete pestoralism and alleged escapism. It seemed as if both the critics and the audience simply failed to understand the subtext of his poems that reveals a magnificent spiritual pilgrimage undertaken by a poet in the age of anxiety. In search of the calm point of his tumultuous universe Brook varies different symbolic patterns and groups of symbols thus disclosing the lasting change of his poetic sensibility that range from purely pagan denial of urban values and the unrestrained blasphemy up to the true Christian piety. Our analysis affirms him the true modernist poet, a cosmopolitan mind, always apt to accumulate new experiences and it is certain that his work will be seen in quite a new light in the decades to come.